Effect of Body Position during Whole Body Vibration on Acute Jumping Performance (Baltic Journal of Sport and Health Sciences, 2016)
Background. The aim of the study was to investigate the acute effect of whole-body vibration (WBV) during heel raised and standing squat position on squat (SJ) and countermovement jump (CMJ) heights.Methods.  Twenty  four  physically  active  sport  science  students  are  voluntarily  participated  in  this  study. Randomized, counterbalanced, crossover study was used in this study and all subjects completed two trials that were plantar (25–30°) and dorsal (5–10°) flexion squats. WBV exercises were performed on a vibration plate at 26 Hz frequency, 4mm amplitude. Jumping performances were assessed with and without WBV conditions. Subjects executed WBV condition treatment on static plantar or dorsal flexion half squat position (45 °knee angle) for 3x60 s with 60 s rest between sets.Results. There was no statistically significant two-way interaction between treatments and times for SJ and CMJ (p > .05). SJ and CMJ after the WBV were significantly higher than without WBV condition (p < .05). SJ and CMJ heights were higher than baseline values without WBV.Conclusion. These  results  indicate  that  there  were  no  differences  between WBV  during  plantar  and  dorsal flexion squat position on SJ and CMJ heights. Regardless of different muscle length squat position during WBV, there were little but significant differences (~1cm) on SJ and CMJ heights after WBV. According to these results it can be said that WBV had a statistically significant acute effect on jumping, but different plantar-flexor muscle length squat position on vibration plate during WBV did not have any effect on jumping performance.Keywords:  whole body vibration, acute effect, body position, jump performance